The Influence of the Gasing Learning Method on the Mathematics Learning Outcomes of Class II Students at SD Negeri 125543 Lapangan Bola - Gultom, Desi Lestari; Panjaitan, Muktar Bahruddin; Tambunan, Janwar (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
This study aims to determine the effect of the GASING (Easy, Fun, and Enjoyable) learning method on the mathematics learning outcomes of second-grade students at SD Negeri 125543 Lapangan Bola. This study uses a quantitative approach with a quasi-experimental method and a pretest–posttest design. The study population was all 26 second-grade students who were also used as samples. The research instrument was a learning outcome test that had been tested for validity, reliability, difficulty level, and discriminatory power. Data were analyzed using a normality test and a hypothesis test (paired sample t-test). The results showed that the average pretest score of students was 22.11 in the low category, while the average posttest score increased to 69.03 in the good category. The hypothesis test showed a significance value of 0.000 less than 0.05, which means there is a significant influence between the application of the GASING method on students' mathematics learning outcomes. Thus, the GASING method is proven to be effective in improving mathematics understanding and learning outcomes quickly, easily, and enjoyably.